ANALISIS STRATEGI BERTAHAN USAHA KERIPIK NENAS KEMASAN DI TENGAH KRISIS EKONOMI AKIBAT TERDAMPAK COVID-19 PADA UMKM USAHA BARU IBU KABUPATEN KAMPAR - Ebean Ezher Batubara; Meyzi Heriyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The world is being hit by a COVID-19 pandemic including Indonesia, to prevent the spread of the COVID-19 virus, the government issued policies that affect community activities that impact almost all sectors of life, sector micro, small and medium enterprises (MSMEs) as one of the economic sectors affected by this pandemic. In order for the sector to continue to survive, MSMEs players must be able to survive by creating various steps or strategies. The problem seen in this study is how the culinary sector MSMEs survival strategy during the COVID-19 pandemic, while the purpose of this study is to find out the strategies used by MSMEs so that they can survive in the of a pandemic. This research uses qualitative research methods, namely research procedures that produce descriptive data in the form of written or spoken words from people and observed behavior. The data study technique was through observation, interview and documentation. The data were analyzed using qualitative analysis techniques. The results show that to survive during the pandemic, MSMEs players have the following strategies, namely, using marketing through social media in the form of instagram, facebook, whatsapp, E-Commerce, improving product and service quality,and optimizing, Costumer Relationship Marketing.   Keywords: COVID-19 Pandemic, Survival Strategy, MSMEs